Frente de agua: regeneración urbana del malecón turístico sobre el río Magdalena (2020)
The project "Water Front: Urban Regeneration of the Tourist Boardwalk on the Magdalena River", proposes, in respect of local planning instruments, to improve sustainability indicators and to give resistance to the urban helmet in environmental, social and cultural controls. Urban cohesion represents a central theme of the proposal since it considers the ways of working of the urban fabric and some subunits of landscape. Likewise, exchanges and access opportunities in the municipality confer territorial balance to the proposal, responding to the crisis in some contexts determined by insecurity, risk, discontinuity, barriers, marginalization, and recognizable urban-social segregation in the current situation. of the city (Municipality of Neiva, 2012) Regenerate the landscape unit that corresponds to the Malecón del Río Magdalena, western edge of the city, which represents one of the few green corridors in the city and is part of the main ecological structure of Neiva. This landscape unit is currently a fully motorized artificial habitat, solid waste dump, garbage dump, residual spaces and housing for street dwellers. Few specific itineraries, compatible uses, or adequate construction treatment, traffic is mainly vehicular through the sector, the place of entry and exit to and from different municipalities and cities. The functionality and spatiality of this landscape unit is a key part of Neiva's configuration, but it is seeing problems due to forgetfulness, abandonment, loss and the lack of use of its environmental, social and cultural values. The aim is to promote, improve and regenerate the boardwalk, influencing the environmental, social and cultural characteristics of the city. To this end we take the Río Magdalena urban-natural border (Malecón Turístico) as a landscape unit. The regeneration is carried out from the urban design thought to promote routes, movements, tensions, itinerant spaces and attractive visual points. The project for the new Magdalena River tourist boardwalk proposed here is expected to improve the sustainability and resilience of the city. In addition, generate a change in the perception of the population to consider the Tourist Boardwalk as a place that belongs to them, where they can feel safe and replicate this sense of collectivity that seeks to infuse the project into other urban voids in the city of Neiva.